EFFECTIVENESS OF SOCIAL SKILLS TRAINING (SST) BASED ON COMPUTER AND MANUAL FOR IMPROVING SOCIALIZATION AND SOCIAL FUNCTION OF SCIZOFRENIA PATIENTS: SYSTEMATIC REVIEW - SITI KOTIJAH; ASEF WILDAN MUNFADLILA (Bina Sehat Press. Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2019)
Background: Schizophrenia is part of a psychotic disorder characterized by a loss of understanding of reality and a loss of insight that can be found in symptoms of severe mental disorders such as hallucinations, delusions, chaotic behavior, and chaotic speech, as well as negative symptoms that cause social damage. Psychosocial interventions such as Social Skills Training (SST) is one of the efforts that can be given to schizophrenic patients with the aim of increasing patient socialization and communication skills so that patients are able to adapt to their environment. Research Objectives: To determine the effectiveness of computer-based and manual-based Social Skills Training (SST) on improving the socialization and social function of schizophrenic patients. Data Sources: Sources of data obtained from Pubmed, Sciencedirect, and Ebsco Inclusion Criteria: 1) research studies using the RCT approach, 2) studies in schizophrenic patients in the adolescent-adult age range (17 years-80 years), 3) studies with social therapy interventions, skills training combined social cognitive therapy therapy treatments, both as independent interventions or in combination with other interventions Appraisal studies and synthesis methods: Appraisal studies use the critical appraisal skills program (CASP), and the synthesis method uses PICO modifications. Results: Social skill training (SST) has a significant influence in overcoming the improvement of socialization and social functions Conclusions and Implications of Results: Social skill training (SST) provides a significant influence in improving socialization and social functions so that it can be applied as an effort to overcome social damage. Keyword: Social Skills Training (SST), Social skill training (SST), Computer and Manual.